“Touring” of Disabled People as Social Problem of 1920s: Search for Solutions (on Materials of Siberia) - A. S. Kovalev (Научный диалог, 2019)
The relevance of the study is due to the need to study the historical features of such a phenomenon as “fraud of the disabled,” which arose in the first decade of Soviet power in the territory of the RSFSR and was called “touring,” when persons who did not have the right to receive social security, received it, attributing the merits of a disabled worker, disabled veteran or disabled old-age. The article analyzes the characteristics of “touring,” allowing to consider the specifics of this phenomenon, familiarity with which leads to the conclusion that it was not only a social problem of the NEP period, but also to a certain extent the way of life of many citizens excluded from society. There are cases of “touring,” helping the reader to understand whether it was a conscious fraud or a way of survival. Attention is paid to the activities of social security bodies and committees for the disabled and the red army soldiers to identify cases of “touring” and the implementation of measures to prevent it, among which there were both legislative attempts to limit the right of the disabled to move within the country, and the systematization, ordering of one-time social payments, as well as other non-standard ways to combat.